Margaret Dibben's Smart Questions to Ask About Money : How to Get What You Really Need and Want - Dibben, Margaret (London Orion Business Books, cop., 1999)
This series is designed to show readers how to get the best service and advice from their professional financial adviser, ensuring that they get what they really want and need. The series is designed to provide readers with all they need to know when asking questions and making decisions
Include Index
Keywords: Great Britain -- Finance, Personal